Room-temperature photodetectors and VOC sensors based on graphene oxide–ZnO nano-heterojunctions. Issue 47 (25th November 2019) - Pargoletti, Eleonora; Hossain, Umme H.; Di Bernardo, Iolanda; Chen, Hongjun; Tran-Phu, Thanh; Lipton-Duffin, Josh; Cappelletti, Giuseppe; Tricoli, Antonio
Abstract : Here, we show 3D nanoarchitectures comprising integrated GO–ZnO heterojunctions for either room temperature sensing of ppb volatile biomarkers or response to UV light, showcasing their applicability as chemoresistors and visible-blind photodetectors. Abstract : The rapid development of smart wearable electronics is driving the engineering of novel miniaturized sensing materials that can rapidly respond to very small changes in the concentration of biomarkers at room temperature. Carbon-based nanomaterials offer numerous attractive properties such as low resistivity, good mechanical robustness and integration potential, but lack a strong detection and transduction mechanism for the measurement of chemical molecules or photons. Here, we present a three-dimensional nanostructured architecture comprising optimally integrated graphene oxide (GO)–ZnO heterojunctions for the room temperature sensing of volatile biomarkers. We show that this layout also provides excellent response to UV light showcasing its applicability as a visible-blind photodetector. Notably, the optimal integration of well-dispersed GO nanodomains in a 3D ZnO network significantly enhances the room-temperature chemical sensitivity and light responsivity, while higher GO contents drastically worsen the material performance. This is attributed to the different roles of GO at low and high contents. Small amounts of GO lead to the formation of electron depleted nano-heterojunctions with excellent electron–hole separation efficiency. In contrast, large amounts of GO form a percolating electrical network that inhibits the light and chemical-sensing properties of the ZnO nanoparticles. Our optimal GO–ZnO demonstrates 33 A W −1 responsivity to UV light as well as the room temperature detection of volatile organic compounds down to 100 ppb. We believe that these findings provide guidelines for the future engineering of hybrid carbon–metal oxide devices for applications extending from optoelectronics to chemical sensing and electrocatalysis.